Carbon dioxide in the prevention of air embolism during open-heart surgery - Ng, W. Shang (1968)
The factors which are important in the design and use of apparatus for the effective displacement of air by carbon dioxide from chest cavities are examined. High levels of carbon dioxide can be achieved by flowing carbon dioxide at a total flow rate of 51./min. into the chest cavity through two nozzles of 0·5 to 1·0 cm. diameter. The effect of factors which might diminish the carbon dioxide levels is examined.